Purpur Sage As A Peacebuilding: The Practice of Purpur Sage As Self-Reconciliation Towards Restoring Relationship with Others - Ginting, Eikel Karunia (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Conflict reconciliation often does not pay attention to the aspect of restoring internal memory as part of restoring relations between problematic parties. It is not uncommon for conflict management to leave scars for the parties involved and requires space to share experiences regarding these wounds, both from the perspective of the perpetrator and the victim. Horizontal conflict resolution is often only carried out as a stage of maintaining peace (pseudo-peace) because it is carried out formally and contains political elements, while the restoration of conflict relations needs to be carried out comprehensively, namely in the memory of individuals. Based on the reality that often after reconciliation, conflict continues to occur because the resolution is not carried out starting from individual awareness. This is what the author will analyze from two research results on reconciliation in Dolat Rayat Village and Seberaya Village. This paper aims to identify the purpur sage concept based on the results of previous research which shows that there is still a vulnerability to conflict during reconciliation. Then this article provides an evaluation based on Miroslav Volf's understanding. The elaboration of the concept of purpur sage and Miroslav Volf's views in this article becomes a recommendation for a more complete and comprehensive reconciliation.